ANALISIS PENGARUH BIAYA PEMASARAN TERHADAP PENDAPATAN PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTAT YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2024 - Kiagus Muhammad Amran; Rama Febriansyach (Universitas Logistik dan Bisnis Internasional, 2026)
The Property and real estate sector is a vital part of indonesia's economy. In 2024, several IDX-listed companies in this sector saw declining revenues despite increased marketing spending, raising concern about cost efficiency. This study aims to analyze marketing expenditures, revenue performance, and the effect of marketing costs on revenue among property and real estate firms listed on IDX in 2024. Using a quantitative approach with secondary financial data, the analysis employed correlation, regression, T-Test, and determination coefficient. Result show that while most companies experienced rising marketing costs alongside higher revenues, some showed the opposite trend. The T-Test indicated a significance value of 0.0001 > 0.05, confirming that marketing expenditures have a positive and significant impact on revenue.